Development of anti-membrane type 1-matrix metalloproteinase nanobodies as immunoPET probes for triple negative breast cancer imaging - Mulero, Francisca; Oteo, Marta; Garaulet, Guillermo; Magro, Natalia; Rebollo, Lluvia; Medrano, Guillermo; Santiveri, Clara; Romero, Eduardo; Sellek, Ricela E.; Margolles, Yago; Campos-Olivas, Ramón; Arroyo, Alicia G.; et al. (Frontiers in Medicine, 2022)
Triple-negative breast cancer (TNBC) is characterized by aggressiveness and high rates of metastasis. The identification of relevant biomarkers is crucial to improve outcomes for TNBC patients. Membrane type 1-matrix metalloproteinase (MT1-MMP) could be a good candidate because its expression has been reported to correlate with tumor malignancy, progression and metastasis. Moreover, single-domain variable regions (VHHs or Nanobodies) derived from camelid heavy-chain-only antibodies have demonstrated improvements in tissue penetration and blood clearance, important characteristics for cancer imaging. Here, we have developed a nanobody-based PET imaging strategy for TNBC detection that targets MT1-MMP. A llama-derived library was screened against the catalytic domain of MT1-MMP and a panel of specific nanobodies were identified. After a deep characterization, two nanobodies were selected to be labeled with gallium-68 (68Ga). ImmunoPET imaging with both ([68Ga]Ga-NOTA-3TPA14 and [68Ga]Ga-NOTA-3CMP75) in a TNBC mouse model showed precise tumor-targeting capacity in vivo with high signal-to-background ratios. (68Ga)Ga-NOTA-3CMP75 exhibited higher tumor uptake compared to (68Ga)Ga-NOTA-3TPA14. Furthermore, imaging data correlated perfectly with the immunohistochemistry staining results. In conclusion, we found a promising candidate for nanobody-based PET imaging to be further investigated as a diagnostic tool in TNBC.